Investigation of Bacteriological Quality of Meat from Abattoir and Butcher Shops in Bishoftu, Central Ethiopia - Abebe Bersisa; Dereje Tulu; Chaluma Negera (International Journal of Microbiology)
The study was conducted from November 2015 to November 2016 to determine bacterial load and identify pathogenic bacteria (S. aureus, E. coli, and Salmonellae species) in meat from abattoir and butcher shops as well as to assess associated hygienic and sanitation practices being experienced in the selected study site. A cross-sectional study was conducted where a simple random sampling method was used to select butcher shops, and the municipal abattoir was purposively selected. A structured questionnaire survey was also used to assess hygienic status of the municipal abattoir and butcher shops. A total of 124 samples (48 swab samples from abattoir carcass, 4 samples of carcass washing water about 20 ml of each, and 36 swab samples each from butcher shop cutting table and cutting knife, respectively) were collected during the study period. The collected samples were processed for aerobic plate count, and the total mean count was found to be 4.53 log10 cfu/cm2 from abattoir carcass swab samples, 2.4 log10 cfu/ml from water samples, 6.58 log10 cfu/cm2 from butcher shops cutting table, and 6.1 log10 cfu/cm2 from cutting knife swab samples. E. coli was the dominant bacterial species isolated (35.2%), followed by S. aureus (22.5%) and Salmonellae species (9.9%). According to the questionnaire survey, 48.4% (15/31) of the abattoir workers did not receive any training regarding food safety issues. Moreover, a majority (66.67%) of the respondents of the butcher house workers were grade 1–4 (elementary) in their educational level and do not use hairnet and handle money with bare hands during serving meat to consumers. The study showed that the hygienic status of the abattoir and butcher shops in the study area is poor, and the obtained results of bacterial load are higher than the acceptable limit of the standard. Therefore, the necessary strategies towards hygiene and sanitation of meat in the town should be implemented.